Ketahanan Ekonomi dan Tantangan Petani Perempuan dalam Usaha Pertanian Kolektif - Anandhiya Intan Prabandari; Sausan Nuhaa Maisaraah; Febyana Putri Komalasari (Universitas Batanghari Jambi, 2026)
This study explores the economic resilience and challenges faced by women farmers engaged in collective agricultural ventures in the districts of Purbalingga, Banjarnegara, and Banyumas, Indonesia. Women farmers’ groups, known locally as Kelompok Wanita Tani (KWT), play a vital role in rural agricultural economies by fostering cooperative farming, knowledge sharing, and mutual support. Despite their contributions, these women encounter multifaceted challenges, including limited access to capital, market barriers, infrastructural constraints, and entrenched gender norms. Employing a mixed qualitative approach of surveys, in-depth interviews, and focus group discussions, this research reveals how KWT membership enhances household income, financial autonomy, and decision-making power among women. Livelihood diversification and social capital emerge as key strategies supporting economic resilience. However, persistent barriers like capital scarcity, infrastructure limitations, and generational engagement risks threaten sustainability. The study recommends targeted policy interventions to strengthen institutional support, financial inclusion, youth engagement, gender-sensitive policies, and market access to sustain and amplify these gains. These findings contribute contextualized insights into women’s economic empowerment through collective agriculture, informing stakeholders on advancing equitable and resilient rural development in Indonesia.